2018
DOI: 10.1111/anae.14211
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of outcomes in postoperative pain studies in paediatric and adolescent patients: towards development of a core outcome set

Abstract: Systematic reviews of postoperative pain in children have called into question the consistency of outcomes measured by clinical triallists as well as the measurement instruments used for assessment. Core outcome set methodology may be a solution to improve standardisation. This study provides an evidence-based foundation for the development of a core outcome set for paediatric postoperative pain studies. We searched ClinicalTrials.gov to identify relevant postoperative pain studies in children. The search yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Our research supports this, as the outcome domains most frequently and consistently reported by trials were 'Neonatal', 'Delivery' and Survival' and these outcomes reflect the questions identified by clinicians and researchers. The lack of patient involvement has become widely recognised and the importance of engaging them in research is being increasingly acknowledged [24,[26][27][28][29]. This is vital as researchers can only be certain that interventions are being evaluated in a way that is relevant to the target population if parents' perspectives are considered [30].…”
Section: Discussionmentioning
confidence: 99%
“…Our research supports this, as the outcome domains most frequently and consistently reported by trials were 'Neonatal', 'Delivery' and Survival' and these outcomes reflect the questions identified by clinicians and researchers. The lack of patient involvement has become widely recognised and the importance of engaging them in research is being increasingly acknowledged [24,[26][27][28][29]. This is vital as researchers can only be certain that interventions are being evaluated in a way that is relevant to the target population if parents' perspectives are considered [30].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies may report changes in outcomes, but the differences, although statistically significant, may not truly matter to patients. Core outcome sets can help in selection and defining outcomes and effect sizes that matter to patients , but in the realms of ACL repair, successful outcome after ACL reconstruction is supposedly not dependant on pain . Therefore, what is clear is that assessment of short‐term pain outcomes, although important, should be supplemented by longer term, patient‐centred outcomes, including function and quality of life assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the presence of post-operative pain at large, despite the availability of various effective anaesthetic techniques and protocols (26). In fact, most physicians believe that the issue in paediatric analgesia is not a lack of effective analgesia for postoperative pain relief, but a lack of accurate assessment of pain and adequate organization of pain treatment (27). The realistic goals of pain treatment in children are to: recognize the pain, anticipate and prevent pain if possible, reduce moderate and severe pain, avoid serious adverse effects, shorten hospital stay, and prevent the development of chronic pain syndromes.…”
Section: Generalizabilitymentioning
confidence: 99%